ANALISIS TINGKAT PENERIMAAN DAN PENGGUNAAN APLIKASI BSI MOBILE MENGGUNAKAN MODEL UTAUT 2 DI DKI JAKARTA - Nadya Gustiana Azzahra (2022)
The world's population now lives in an era of digital transformation due to the quick advancement of information technology. The COVID-19 pandemic, which has altered society's transactional features, is a driving force behind the current, faster digital revolution. This has caused a number of changes, including an increase in non-cash transactions and a decline in bank branch locations. Utilization of mobile banking apps, such as Bank Syariah Indonesia(BSI), has expanded in Indonesia as a result of the trend of digitization. Significant growth was seen in BSI clients, although only 10% of those customers regularly use BSI Mobile. Therefore, the purpose of this study is to analyze the level of acceptance and use of customers using BSI Mobile using UTAUT 2 theory which was modified with the addition of the religiosity. The method used in this study is a quantitative using primary data sources and secondary data analyzed using SEM-PLS. The results of this study indicate that performance expectations, effort expectations, social factors, facilitating conditions, hedonic motivation insignificant interest in using BSI Mobile, but are influenced by price values, habits and religiosity. then usage interest doesn't affect the behavior of using BSI Mobile, but is influenced by facilitating conditions and habits.